2020
DOI: 10.1111/anae.14995
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effective pre‐oxygenation interval in obstetric patients using high‐flow nasal oxygen and standard flow rate facemask: a biased‐coin up–down sequential allocation trial

Abstract: Summary Using biased‐coin sequential allocation, we sought to determine the effective time interval in 90% of healthy parturients to achieve a target endpoint end‐tidal oxygen of ≥ 90% using standard flow rate facemask and high‐flow nasal oxygen. Eighty healthy parturients were randomly assigned to standard facemask (n = 40) or high‐flow nasal oxygen (n = 40) groups; half of the parturients in the high‐flow nasal oxygen group also used a simple no‐flow facemask to minimise air entrainment. The effective time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
(45 reference statements)
0
24
0
Order By: Relevance
“…However, we learned from our two recent studies that even when instructed, most parturients were unable to tolerate high‐flow nasal oxygen of 50–70 l.min ‐1 with closed mouth breathing 100% of the time . In fact, we found that only 37.5% of parturients were able to breathe high‐flow nasal oxygen with their mouths closed . Expiratory pharyngeal pressure is significantly lowered when breathing with the mouth open .…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…However, we learned from our two recent studies that even when instructed, most parturients were unable to tolerate high‐flow nasal oxygen of 50–70 l.min ‐1 with closed mouth breathing 100% of the time . In fact, we found that only 37.5% of parturients were able to breathe high‐flow nasal oxygen with their mouths closed . Expiratory pharyngeal pressure is significantly lowered when breathing with the mouth open .…”
mentioning
confidence: 82%
“… found high‐flow nasal oxygen at 50 and 70 l.min ‐1 resulted in nasopharyngeal airway pressures as high as 6.8 and 10.1 cmH 2 O, respectively, in healthy volunteers when breathing with their mouth closed. However, we learned from our two recent studies that even when instructed, most parturients were unable to tolerate high‐flow nasal oxygen of 50–70 l.min ‐1 with closed mouth breathing 100% of the time . In fact, we found that only 37.5% of parturients were able to breathe high‐flow nasal oxygen with their mouths closed .…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…I compliment Au et al. for their recent publication on the role of high‐flow nasal oxygenation in obstetric patients . They call attention to the fact that it took more than 8 min for 90% of parturients to attain an end‐tidal oxygen saturation of ≥ 90%.…”
mentioning
confidence: 88%
“…The recent focus of attention on preventing hypoxia during induction of general anaesthesia has been on defining a role for high-flow humidified oxygen, but benefits of this equipment as a preoxygenation tool in obstetric patients have not been demonstrated. 7,8 Considering the cost implications and lack of evidence, it would be unjustified presently to recommend this as a standard of care in resource-constrained settings. However, several simple low-cost strategies should always be undertaken when providing general anaesthesia to an obstetric patient.…”
mentioning
confidence: 99%